Concussion causes transient dysfunction in cortical inhibitory networks but not the corpus callosum - Hammond-Tooke, G.D.; Goei, J.; du Plessis, L.J.; Franz, E.A. (Journal of clinical neuroscience, 2010)
The corpus callosum (CC) is thought to be especially vulnerable in traumatic brain injury. Bimanual cost (a slowing of reaction time with bimanual compared to unimanual responses) is a sensitive indicator of CC function. To determine whether CC dysfunction is a significant feature of mild traumatic brain injury, unimanual and bimanual reaction times were studied in 10 recently concussed patients and 10 healthy participants. Reaction times were studied within 1 week of concussion and again after 1 month. Concussion symptoms were assessed with the Rivermead Postconcussion Symptoms Questionnaire. The bimanual cost was present at both testing sessions in patients and healthy controls. Although overall reaction times were slower in concussed patients during session 1, these had improved by session 2, as did the symptom scores. These findings suggest that the pathogenesis of mild traumatic brain injury involves intrahemispheric cortical networks rather than impaired interhemispheric communication via the CC.